2014
DOI: 10.1371/journal.pone.0098545
|View full text |Cite
|
Sign up to set email alerts
|

Current Situation and Associated Factors of Withdrawing or Withholding Life Support to Patients in an Intensive Care Unit of Cancer Center in China

Abstract: ObjectivesTo investigate the current situation and analyze the associated factors of withdrawing or withholding life support in the intensive care unit (ICU) of our cancer center.MethodsThree hundred and twenty-two cancer patients in critical status were admitted to our ICU in 2010 and 2011. They were included in the study and were classified into two groups: withdrawing or withholding life support (WWLS), and full life support (FLS). Demographic information and clinical data were collected and compared betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Furthermore, it should be noted that, in almost 10% of patients with documented treatment limitations (WhWd) in this form, the accompanying DNR decision was not formally registered at the same time; this can perhaps be attributed to oversights when filling out the HELICS-ICU form, which should ideally be minimized. When compared to other published works, it becomes clear that there is room for improvement, but also that this problem persists in several other ICUs: several Asian centers go into detail regarding the intervening elements in the decision process, demonstrating a considerable input from family members or surrogates while very little contribution from nursing staff 11,12 ; a French study by Lesieur et al 1 developed a specific form to document reasons for WhWd decisions, participants, and type of treatment withheld. Esteban et al 17 also recorded specific data pertaining to the participants in the decision and the type of discussion with family members or surrogates.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it should be noted that, in almost 10% of patients with documented treatment limitations (WhWd) in this form, the accompanying DNR decision was not formally registered at the same time; this can perhaps be attributed to oversights when filling out the HELICS-ICU form, which should ideally be minimized. When compared to other published works, it becomes clear that there is room for improvement, but also that this problem persists in several other ICUs: several Asian centers go into detail regarding the intervening elements in the decision process, demonstrating a considerable input from family members or surrogates while very little contribution from nursing staff 11,12 ; a French study by Lesieur et al 1 developed a specific form to document reasons for WhWd decisions, participants, and type of treatment withheld. Esteban et al 17 also recorded specific data pertaining to the participants in the decision and the type of discussion with family members or surrogates.…”
Section: Discussionmentioning
confidence: 99%
“…Their median age was 62 years (IQR: 51-72 years), and there were 891 (59%) male patients. The median APACHE and SAPS II scores were 16 (IQR: [11][12][13][14][15][16][17][18][19][20][21][22][23][24] and 38 (IQR: 29-55), respectively. Total ICU mortality was 16.3% (247 patients), and hospital mortality was 39% (590 patients).…”
Section: Patients' Characteristicsmentioning
confidence: 99%
“…One study reported that extubation before the patient's death was associated with better family satisfaction with medical care [18]. Some research has focused on factors related to withdrawal of MV [4,19], and the perceptions [7] or satisfaction [18] of patients' families. In 2016, there were several studies on family preparation [20], communication [21,22], and support before and during LST withdrawal [20].…”
Section: Introductionmentioning
confidence: 99%